Democracia e território: reflexões sobre a construção de uma prática democrática participativa - Almeida, Layssa Ramos Maia de (2019)
This dissertation aims to resume the discussion on the relationship between democracy and territory, identifying the main elements capable of influencing the possibility of building a more participatory democratic practice. Therefore, we sought to map the theoretical and practical interfaces historically constructed between these two concepts in order to understand their apparent distancing in current times. Thus, it was important to rescue the process of building the representative hegemonic democratic model and the influence of neoliberal politics in the configuration of territories, observing the impacts of these elements in the constitution of a very limited democratic practice for the majority of the population. Contrary to the alternatives of popular participation created within the traditional democratic institutionality, this research proposes the discussion about participatory democracy in dialogue with the perspective of popular organization in the territory, seeking to structure collective, autonomous and solidary practices. Based on this reflection, the analysis, based on secondary data, is made of two experiences: the Communal Councils and the Communes, in Venezuela and the Territories of Citizenship Program, in Brazil, through the study of political contexts and implementation history, the territorial arrangements created, their relationship with the different scales, as well as their commitment to political and cultural formation and to the association with a broader policy of social transformation. In short, the analysis identified three central elements: the strong conflict between traditional representative structures and those organized from the territory; the permanent contradiction in the relation of these experiences with the state and the capitalist system and, finally, the necessity of these experiences to focus on the construction of new forms of social and economic relations, pointing towards a structural transformation of society.